Undesired Behaviours in Preschool Classrooms and the ways for Coping with these Behaviours - Merve Gangal; Yasin Öztürk (Anı Publishing, 2019)
In this study, it is aimed to classify the children's undesired behaviours that teachers are faced in preschool classrooms, and the ways of teachers' coping with these behaviours. As a qualitative methodology, the case study was used for the research procedure. The participants of the study are three preschool teachers working in Trabzon. The data of the study was obtained from unstructured classroom observations, semi-structured interviews with teachers and document analysis of the teacher's daily plans. The data was analysed through content analysis by a qualitative data analysis tool, NVivo 8. As a result, undesired behaviours in class classified under four headings; nonproblem ,minor problem, major problem limited in scope and effects   and escalating or spreading problem. The teacher's coping strategies with the misbehaviours in classrooms were classified under two headings: commonly used methods and uncommon strategies/methods.  Finally, this study showed that the methods and the strategies under the heading of the commonly used methods were more frequently applied according to the uncommon strategies/methods.